Citrullinated peptides of peptidyl arginine deiminase 4 as major B-cell epitopes in patients with rheumatoid arthritis - Giassi, Mathilde; Toussirot, Eric; Lambert, Nathalie C.; Roudier, Jean; Auger, Isabelle (Frontiers in Immunology, 2025)
ObjectiveTo identify new autoantibodies in rheumatoid arthritis (RA) patients’ sera.MethodsWe tested serum samples from 55 patients with RA and 25 controls on arrays containing 188 peptides from the alpha and beta chains of fibrinogen, vimentin, histon 4, enolase, proteoglycan, filaggrin, collagen, and human peptidyl arginine deiminase 4 (hPAD4). To confirm the validity of our peptide array detection, we tested serum samples from 50 patients with RA and 42 controls on purified peptides by luminescent enzyme-linked immunosorbent assay (ELISA).ResultsWe found citrullinated peptides from hPAD4 that were recognized almost uniquely by sera from patients with RA on peptide arrays and ELISA. Peptide P22/60 from hPAD4 is a better RA diagnostic tool than the major classical citrullinated B-cell epitopes from histon 4, proteoglycan, alpha fibrinogen, and enolase.ConclusionWe identified citrullinated peptides from hPAD4 as RA-specific autoantigens.